Study on indium leaching from mechanically activated hard zinc residue - Yao J.H.; Li X.H.; Li Y.W. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this study, changes in physicochemical properties and leachability of indium from mechanically activated hard zinc residue by planetary mill were investigated. The results showed that mechanical activation increased specific surface area, reaction activity of hard zinc residue, and decreased its particle size, which had a positive effect on indium extraction from hard zinc residue in hydrochloric acid solution. Kinetics of indium leaching from unmilled and activated hard zinc residue were also investigated, respectively. It was found that temperature had an obvious effect on indium leaching rate. Two different kinetic models corresponding to reactions which are diffusion controlled, [1-(1- x)1/3]2=kt and (1-2x/3)-(1-x)2/3=kt were used to describe the kinetics of indium leaching from unmilled sample and activated sample, respectively. Their activation energies were determined to be 17.89 kJ/mol (umilled) and 11.65 kJ/mol (activated) within the temperature range of 30°C to 90°C, which is characteristic for a diffusion controlled process. The values of activation energy demonstrated that the leaching reaction of indium became less sensitive to temperature after hard zinc residue mechanically activated by planetary mill.